Modulation of Emission Intensities of Binary Films Composed of Fluorescent Amorphous Molecular Materials and p‐Toluenesulfonic Acid in Response to Exhaled Breath. Issue 8 (17th June 2016) - Nakano, Hideyuki; Nishimura, Tomohiro; Nagata, Eisuke; Ichikawa, Ryoji
Abstract: We have found that fluorescence emission of binary films composed of fluorescent amorphous molecular materials, 4‐[bis(4‐methylphenylaryl)amino]benzaldehyde (BMABA) and 4‐[bis(4‐methylphenylaryl)amino]acetophenone (BMAAP), with p ‐toluenesulfonic acid (TsOH) was quenched at ambient dry atmosphere but enhanced when we breathed onto their films. When pausing the breath, the emission was again quenched. Moisture in the exhaled breath was suggested to play a role for such phenomena. It was suggested that some BMABA and BMAAP molecules were protonated in their films as prepared at ambient dry atmosphere and that protonation and deprotonation took place corresponding to change in surrounding humidity, resulting in modulation of emission intensity. Abstract : Novel binary films composed of emitting amorphous molecular materials (BMABA and BMAAP) with p ‐toluenesulfonic acid (TsOH) were found to exhibit modulation of emission intensities in response to exhaled breath.